Practice Change as a Local Economic Development Strategy: A Market Access Perspective - Nanthakumaran, R.; Morais, N.; Mangaleswaran, T.; Ravikumar, R. (Vavuniya Campus of the University of Jaffna, 2008)
This paper discusses the role of practice change in economic empowerment of rural communities. The concept of practice change refers to the adoption of standard practices in production and marketing activities. Adoption of standard practices is placed in a broader perspective to explain its facilitative role in improving market access and promoting rural livelihoods. The study adopted quantitative, qualitative and participatory methods to examine the role of practice change in promoting rural livelihoods. Multiple methodologies were used to triangulate the data. For quantitative information we carried out a household questionnaire survey. A sample of 80 members, who received cattle during the first two distributions, was selected for the survey. Qualitative information was obtained from semi structured interviews with different stakeholders that included veterinary doctors, programme staffs of implementing NGOs, members of the district level advisory committee and representatives of other relevant government departments. We also adopted a participatory method of conducting focus group discussions with executive members of the cooperatives, field based animal health workers and field staffs of the supporting NGOs. In addition the research team also made several field visits to observe the small holding farms. The survey was carried out from 1- 30 June, 2008. The study found that 80% of the target farmers have accepted and adopted standard dairying practices in the major areas of breeding, feeding, milking and animal health care. Of this, 40% has adopted fully intensive method and 60% has advanced to semi-intensive method. Although adopted, in the areas of breeding and feeding a significant percentage of farmers (40%) had difficulty in internalizing the practices due to embedded nature of their previous perceptions. Adoption and internalization of standard livelihood practices can positively contribute to promotion of rural livelihoods, which can then lead to improved income of the rural households. When the change is participatory, where the community plays an important role in adopting standard practices, the change can be progressively internalized and sustained.